Detection of Artificially Generated Seismic Signals Using Balloon‐Borne Infrasound Sensors - Siddharth Krishnamoorthy; Attila Komjathy; Michael T. Pauken; James A. Cutts; Raphael F. Garcia; David Mimoun; Alexandre Cadu; Anthony Sournac; Jennifer M. Jackson; Voon Hui Lai; Daniel C. Bowman (Geophysical Research Letters)
Abstract We conducted an experiment in Pahrump, Nevada, in June 2017, where artificial seismic signals were created using a seismic hammer, and the possibility of detecting them from their acoustic signature was examined. In this work, we analyze the pressure signals recorded by highly sensitive barometers deployed on the ground and on tethers suspended from balloons. Our signal processing results show that wind noise experienced by a barometer on a free‐flying balloon is lower compared to one on a moored balloon. This has never been experimentally demonstrated in the lower troposphere. While seismoacoustic signals were not recorded on the hot air balloon platform owing to operational challenges, we demonstrate the detection of seismoacoustic signals on our moored balloon platform. Our results have important implications for performing seismology in harsh surface environments such as Venus through atmospheric remote sensing.